Dengue’s transmitting vector susceptibility to temephos, Trujillo, Peru - Chávez, Julio (2005)
Objective: To determine resistance levels to temephos in Aedes aegypti strains from Trujillo. Material and Methods: The larvae bioassays were done according to the World Health Organization’s methodology. Third or early fourth stage larvae from each population were used, including the reference Rockefeller stock. Five replications from each insecticide concentration were done with mortalities varying between 2 and 98%. Results: All studied strains were susceptible to temephos, with Florencia de Mora showing de highest resistance ratio with 3,05 X value. Conclusion: Continuous resistance to temephos monitoring should be carried out in A. aegypti strains in order to decide on the correct use of this insecticide.